Fox Temple, Shenyang, 1909 - Unknown (University of Southern California Digital Library (USC.DL), 2014)
“This is the ‘Fox Temple’ close to the ‘Small River Bank’ at Moukden [Shenyang] where our Kun Kwang School, Hospitals & medical college are. ❧ The Chinese regard the fox as having supernatural qualities, & thus raise temples, & make votive offerings to the fox. At the same time the fox skins are valuable, & so most Chinese seem to have no objection to shooting foxes, & selling their furs. ❧ White foxes (rather rare) are supposed to have extra special powers. I knew a man once who told me that he had once had the temerity to shoot at a white fox, & to his horrified surprise, he saw the bullet stot off the animal’s shin, & fall harmless to the ground. He was quite annoyed when I laughed at this tall story.”